Catalyst-Free and Highly Selective N,N-Diallylation of Anilines in Aqueous Phase - Zhengyin Du; Xiaohong Wei; Wenwen Zhang; Yuanmin Zhang; Qunji Xue (Journal of Chemistry)
A highly selective diallylation reaction of anilines with allyl bromide was achieved in aqueous alcohol solution in the presence of potassium carbonate and without the use of any catalyst. The reaction tolerates a wide range of functionalities, and various tertiary amines were obtained in the yield of up to 99% with complete conversion of anilines.